Ineffective penicillin treatment and absence of partner treatment may drive the congenital syphilis epidemic in Brazil - Swayze, Emma J. (2022)
BACKGROUND: Reducing congenital syphilis has been the focus of Brazilian health programs for decades, yet the cases continue to increase. Although health interventions have targeted HIV screening and treatment, syphilis management continues to be challenging. Syphilis during pregnancy may enhance the HIV maternal seroconversion risk. The potential factors fueling the syphilis epidemic were evaluated in south Brazil, an area of high HIV or syphilis endemicity. OBJECTIVE: We hypothesized that ineffective treatment because of a lack of partner treatment, late presentation to care, and reinfection of previously treated mothers were potential drivers of syphilis mother-to-child transmission. STUDY DESIGN: Data on women diagnosed with syphilis during pregnancy between January 1, 2008 and December 31, 2018 were obtained from a large urban hospital in Porto Alegre, Brazil. The patients were stratified into effective vs ineffective treatment groups according to the World Health Organization guidelines. Crude and adjusted risk ratios for the prediction of congenital syphilis and adverse fetal or neonatal outcomes were computed using Poisson regression. RESULTS: Nearly 56,000 pregnant women delivered over the 11-year period; 1541 (2.8%) had confirmed syphilis during pregnancy, with 934 (61%) receiving ineffective syphilis treatment because of late presentation and diagnosis, delayed treatment initiation, and loss to follow-up with no treatment recorded. Ineffective treatment was associated with maternal education, prenatal care, timing of syphilis diagnosis, venereal diseases research laboratory titers, and maternal HIV coinfection. On multivariate regression analysis, ineffective treatment (adjusted risk ratio, 4.52; 95% confidence interval, 2.35–8.69), absence of prenatal care (adjusted risk ratio, 9.31; 95% confidence interval, 3.77–23.0), syphilis diagnosis at delivery (adjusted risk ratio, 3.08; 95% confidence interval, 2.07–4.58), and maternal nontreponemal titers ≥1:64 (1.09–1.93) were associated with an increased risk of fetal loss. Ineffective treatment (adjusted risk ratio, 1.71; 95% confidence interval, 1.59–1.84), year of diagnosis 2014 to 2016 (adjusted risk ratio, 1.07; 95% confidence interval, 1.02–1.13), absence of prenatal care (adjusted risk ratio, 1.44; 95% confidence interval, 1.17–1.76), and maternal nontreponemal titers >1:4 were associated with an increased risk of congenital syphilis. Although partner treatment reduced the congenital syphilis risk (adjusted risk ratio, 0.60; 95% confidence interval, 0.55–0.66), only 31.8% of partners received treatment. Maternal HIV coinfection was not associated with an increased risk of fetal loss, low birthweight, preterm birth, congenital syphilis, or symptomatic neonatal infection. CONCLUSION: Public health initiatives promoting effective syphilis treatment in pregnancy, increased access to high-quality prenatal care, and partner treatment should be considered to reduce congenital syphilis.